The Communicative Function of English Parenthetical Constructions - Marine Yaghubyan (Armenian Folia Anglistika, 2018)
The main function of parenthetical constructions is to characterize the sentence from the position of the speaker to the listener. In English parenthetical constructions are essential, since they not only connect ideas, sentences, paragraphs making them more cohesive, but also introduce contrast or opposition, emphasis or agreement, purpose, result or conclusion, etc.